Euthymios the Athonite, Greek-Georgian and Georgian-Greek Translator – and Metaphrast? - Høgel, Christian (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2022)
The word Metaphrast has turned up several times in scholarship when de- aling with the prolific, tenth-eleventh-century translator Euthymios the Hagiori- te, also called Euthymios the Iberian (i.e. the Georgian; d. 1028), now especially known for his Greek version of the Barlaam and Ioasaph (or Josaphat) story (henceforth Barlaam)